Clinical Efficacy of Budesonide/Glycopyrronium Bromide/Formoterol in the Treatment of Patients with Acute Respiratory Distress Syndrome and Its Effect on Inflammatory Factors. (28th April 2022) - Liu, Haiying; Wang, Zhengyan; Ren, Lijun; Zhang, Guiqin; Zhao, Dan; Guo, Yanli; Wang, Lijuan; Feng, Hong
Abstract : Objective . To examine the clinical efficacy of budesonide/glycopyrronium bromide/formoterol (Breztri Aerosphere) as an adjunct to acute respiratory distress syndrome (ARDS). Methods . A prospective study enrolled 120 patients with pulmonary endogenous ARDS admitted to the Department of Critical Care Medicine at the Fourth Hospital of Baotou from January 2017 to January 2020, and all enrollments were assigned (1 : 1) to receive conventional treatment (control group) or Breztri Aerosphere (study group). Results . Breztri Aerosphere was associated with a significantly higher total efficacy versus conventional treatment. Breztri Aerosphere resulted in significantly lower acute physiology and chronic health evaluation scoring system (APACHE II) scores and Murray lung injury scores versus conventional treatment. Both groups saw an increase in the partial pressure of carbon dioxide (PCO2), partial pressure of oxygen (PO2), and oxygen saturation (SaO2) after treatment, with higher levels seen in patients given Breztri Aerosphere. After treatment, systemic vascular resistance (SVR) in both groups rose markedly, with greater elevation witnessed in the study group. The patients given Breztri Aerosphere showed significantly lower levels of pulmonary vascular resistance (PVR), mean pulmonary arterial pressure (MAPA), pulmonary artery wedge pressure (PAWP), interleukin-6 (IL-6), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF- α ), and procalcitonin (PCT) versus those receiving conventional treatment. The patients experienced shorter mechanical ventilation time and intensive care unit (ICU) time after treatment of Breztri Aerosphere versus conventional treatment. Conclusion . Adjuvant therapy with Breztri Aerosphere in ARDS can significantly lower APACHE II scores and Murray lung injury scores, improve blood gas indexes and pulmonary circulation function indexes, and shorten mechanical ventilation time and ICU time, which may be attributed to its improvement of organism inflammation status and reduction of inflammatory factors.